Assessment of the Antioxidant Capacity of Standard Compounds and Fruit Juices by a Newly Developed Electrochemical Method: Comparative Study with Results from Other Analytical Methods. Issue 8 (16th June 2015) - Gualandi, Isacco; Ferraro, Luca; Matteucci, Pietro; Tonelli, Domenica
Abstract The antioxidant capacity (AOC) of some standard compounds and commercial beverages was determined using an electroanalytical method which measures the OH radical scavenging ability (OH‐RSC). It is based on the degradation of a thin polyphenol film electrodeposited on glassy carbon following the attack by OH radicals produced by hydrogen peroxide photolysis. The degradation is prevented in presence of increasing concentrations of antioxidants. The same samples were also analyzed by DPPH, ABTS, and ORAC assays. The OH‐RSC method provided AOC values highly correlated with those resulting from the application of ORAC assay for both juices (R=0.90) and standard antioxidants (R=0.96).